(untitled) (Nigerian Journal of Technology, 2018)
A modified memristor chaotic oscillator is proposed for a class of four dimensional chaotic systems. This modification can serve as an alternative way of designing the memristor circuit. We used the passive control technique which requires a single controller to stabilize the system which is presented in our numerical simulations for validation. Our results show that the passive control technique is a very effective technique for controlling chaotic systems. http://dx.doi.org/10.4314/njt.v37i2.25